ANALISIS PENERAPAN PROGRAM SEKOLAH SEHAT DALAM MENINGKATKAN KESADARAN SISWA TENTANG PENTINGNYA MENJAGA LINGKUNGAN DI SDN KEBON JERUK 08 - Hamidah, Fitria; Luthfia Rosidin; Nasywa Nathania; Ranita Fitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze the implementation of the Healthy Schools program in increasing students' awareness of the importance of protecting the environment in State Elementary Schools (SDN). The problem underlying this research is students' low awareness of the importance of maintaining cleanliness and environmental sustainability, which can have a negative impact on the health and quality of the school environment. This research uses descriptive qualitative methods to get an in-depth picture of the implementation of the Healthy Schools program and its influence on student behavior. Data was collected through observation, in-depth interviews with teachers and students, as well as analysis of documents related to the Healthy Schools program. The research results show that the implementation of the Healthy School program in SDN has been carried out through various activities such as health education, cleanliness campaigns, and waste management practices. These findings indicate an increase in students' awareness of the importance of protecting the environment, which is reflected in changes in students' behavior in keeping the classroom and school environment clean. Overall, this research concludes that the Healthy Schools program has a positive contribution in increasing students' awareness of the importance of protecting the environment. However, ongoing support from the school and parents is needed to ensure that this awareness continues to grow and becomes part of students' everyday culture.